101k views
0 votes
What is the simplified form of the following expression? 7(^3 square root 2x) - 3 (^3 square root 16x) -3 (^3 square root 8x)

What is the simplified form of the following expression? 7(^3 square root 2x) - 3 (^3 square-example-1
User ZaPlayer
by
5.7k points

1 Answer

7 votes

Answer:

The third option listed:
\sqrt[3]{2x} -6\sqrt[3]{x}\\

Explanation:

We start by writing all the numerical factors inside the qubic roots in factor form (and if possible with exponent 3 so as to easily identify what can be extracted from the root):


7\sqrt[3]{2x}  -3\sqrt[3]{16x} -3\sqrt[3]{8x} =\\=7\sqrt[3]{2x}  -3\sqrt[3]{2^32x} -3\sqrt[3]{2^3x} =\\=7\sqrt[3]{2x}  -3*2\sqrt[3]{2x} -3*2\sqrt[3]{x}=\\=7\sqrt[3]{2x}  -6\sqrt[3]{2x} -6\sqrt[3]{x}

And now we combine all like terms (notice that the only two terms we can combine are the first two, which contain the exact same radical form:


7\sqrt[3]{2x}  -6\sqrt[3]{2x} -6\sqrt[3]{x}=\\=\sqrt[3]{2x} -6\sqrt[3]{x}

Therefore this is the simplified radical expression:
\sqrt[3]{2x} -6\sqrt[3]{x}\\

User Darc
by
4.9k points